Pengaruh Profesional Competence dan Training Intervention Terhadap Efektivitas Kerja Pegawai di Yayasan Teratai Putih Global - Sukmajati, Indra; Puspasari, Aprilia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Teratai Putih Global Foundation is a social institution in the field of education and community development that requires employees with high work effectiveness. This study aims to analyze the influence of Profesional Competence and Training Intervention on employee work effectiveness using an quantitative method through questionnaires distributed to 50 respondents, with data analyzed using SPSS 27. The findings indicate that Profesional Competence has a positive and significant effect on work effectiveness (t = 3.305; sig. 0.002), while Training Intervention demonstrates a stronger influence (t = 5.222; sig. 0.001). Simultaneously, both variables have a significant effect (F = 127.654; sig. 0.001), with a coefficient of determination (R²) of 0.838, meaning that 83.8% of the variation in work effectiveness can be explained by these two variables.